MTA1: A Prognosis Indicator of Postoperative Patients with Esophageal Carcinoma - Song, Liang; Wang, Zhou; Liu, Xiangyan (The Thoracic and Cardiovascular Surgeon, 2013)
Background To investigate the overexpression of Metastasis-associated gene 1(MTA1) protein and its relationship to the prognosis in esophageal squamous cell cancer after esophagectomy.Methods 174 patients with middle third squamous cell carcinoma of the esophagus underwent complete resection in Provincial Hospital Affiliated to Shandong University between January 2002 and January 2005. The overexpression of MTA1 protein was detected by immunohistochemistry. Kaplan–Meier method was performed to calculate the survival rate, Cox regression multivariate analysis was performed to determine independent prognostic factors.Results MTA1 protein overexpression rate in T1, T2, and T3 patients was separately 25.0, 31.9, and 53%, the difference of MTA1 protein overexpression between them was statistically significant (p = 0.017). The overexpression of MTA1 protein in patients with lymph node metastasis was significantly higher than those without metastasis (p = 0.042). MTA1 protein overexpression correlated with significantly worsened 5-year survival for all patients as well as those with T2 and T3 tumors, N0 nodal status or N1 nodal status. However, no significant correlations with T1 patients (p = 0.061). The result of Cox analysis demonstrated that N stage and MTA1 protein overexpression were independent prognostic factors.Conclusion MTA1 protein overexpression was detected in esophageal squamous cell carcinoma and was found to be significantly associated with the T stage. The patients with MTA1 protein overexpression had a significantly lower 5-year survival rate than without MTA1 protein overexpression. Lymph node metastasis and MTA1 protein overexpression were independent prognostic factors.
Keywords: esophageal neoplasms; lymphatic metastasis; surgical procedures; metastasis-associated gene 1